2021
DOI: 10.1101/2020.12.31.425021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive mapping of mutations to the SARS-CoV-2 receptor-binding domain that affect recognition by polyclonal human serum antibodies

Abstract: The evolution of SARS-CoV-2 could impair recognition of the virus by human antibody-mediated immunity. To facilitate prospective surveillance for such evolution, we map how convalescent serum antibodies are impacted by all mutations to the spike’s receptor-binding domain (RBD), the main target of serum neutralizing activity. Binding by polyclonal serum antibodies is affected by mutations in three main epitopes in the RBD, but there is substantial variation in the impact of mutations both among individuals and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
166
2
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(174 citation statements)
references
References 64 publications
3
166
2
3
Order By: Relevance
“…These antibodies target epitopes that overlap or are closely associated with RBD residues K417, E484 and N501. They are frequently sensitive to mutation in these residues and select for K417N, E484K and N501Y mutations in SARS-CoV-2 S protein expression libraries in yeast and VSV 12,15,33 . To avert selection and escape, antibody therapies should be composed of combinations of antibodies that target non-overlapping or highly conserved epitopes 8,12,13,33,[40][41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These antibodies target epitopes that overlap or are closely associated with RBD residues K417, E484 and N501. They are frequently sensitive to mutation in these residues and select for K417N, E484K and N501Y mutations in SARS-CoV-2 S protein expression libraries in yeast and VSV 12,15,33 . To avert selection and escape, antibody therapies should be composed of combinations of antibodies that target non-overlapping or highly conserved epitopes 8,12,13,33,[40][41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether plasma from vaccinated individuals can neutralize circulating SARS-CoV-2 variants of concern and mutants that arise in vitro under antibody pressure 12,13 , we tested vaccinee plasma against a panel of 10 mutant pseudotype viruses including recently reported N501Y (B1.1.7 variant), K417N, E484K and the combination of these 3 RBD mutations (501Y.V2 variant) [14][15][16][17][18][19] . Vaccinee plasma was significantly less effective in neutralizing the HIV-1 virus pseudotyped with certain SARS-CoV-2 mutant S proteins ( Fig.…”
Section: Vaccine Plasma Binding and Neutralizing Activity Against Sarmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a lot of attention has been focused on RBD mutation E484K, which has emerged in multiple independently SARS-CoV-2 lineages 63, 64 and can alter the antigenicity of the spike protein [65][66][67] . Another naturally occurring RBD mutation, K417N, which has emerged in South Africa and Brazil (B.1.351 lineage and B.1.1.28, respectively) 63, 64,68 , has recently been shown to also alter antigenicity of the spike protein 66,[69][70][71] . Consistently, we found that K417N dramatically decreased the binding of COV107-23 (clonotype 1) and COVD21-C8 (clonotype 2)…”
Section: Discussionmentioning
confidence: 99%
“…C121 escape mutations at 171 E484 were observed in vitro 14 . Mutations at this residue, present also in the novel South African variant (501Y.V2), reduce neutralization by human sera more than 10-fold 21 . E484D affects intermolecular H-bonds at the core of the C121/RBD interface (Fig.2j) and it is suggested to increase the RBD affinity for ACE2 22 .…”
mentioning
confidence: 97%